Infrequent case of intestinal occlusion due to ileum volvulus - Martha Campos Muñoz; Mislay Rodriguez Garcia; Osmel Daniel Chacon Reyes; Daniela De la Caridad Rodriguez Campos; Frank Ariel Castañeda Urdaneta (Revista Cubana de Medicina Militar)
Introduction: Mechanical intestinal occlusion is a common disease in surgical services, however small bowel volvulus is one of its rare causes. Objectives: To describe the clinical characteristics of a case of intestinal occlusion due to ileum volvulus. Clinical case: A 63-year-old male patient, with a history of ethylism and chronic pancreatitis, for which he did not have regular treatment. He went to emergency due to abdominal pain of approximately 24 hours of evolution. He presented two vomits with food debris, without fever or other symptoms of interest. Semiotechnically the pain was maintained, diffuse throughout the abdomen, intense, stabbing, it was not relieved with analgesics. No other accompanying symptoms. Laboratory and imaging studies were performed, the results were suggestive of an occlusive and/or perforative syndrome. Surgical treatment was decided, an intestinal occlusion was diagnosed by ileum volvulus. Conclusions: The diagnosis of the small intestine volvulus requires a high index of suspicion, due to the infrequent occurrence in the adult. Image findings are useful in early diagnosis. The treatment is eminently surgical; Intestinal resection of the affected segment is imposed as long as the intestinal tissue is not viable.